(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
In this look at the Cuban historiography concerning the marginality of the black in the liberating army, the most significant works that approach this problematic in Cuba are analyzed. There is revealed that today, after 115 years of the beginning of the independence exploit, it continues without existing a complete corpus of this phenomenon that gathers the social behavior during the whole warlike contest (1868-1898) and that is centred by on the rebellious army. In addition, the study noticed that the marginality, the discrimination and the racism - between the most marked inheritances with the slavery and with the culture that from this one begins in Cuba - was a problem that, though it also affected certain leaders of black race, for the most part it harmed to the most deprived rebellious blacks, and due to this it was more difficult to detect, exemplify and consider as a problem that existed in the rows of the Cuban revolutionaries. Finally, it is made a recommendation on how to channel the analysis of this still in force problematic in the black population in Cuba, interlacing the different social links that join it.